MOTIVASI BELAJAR WARGA BELAJAR PROGRAM PAKET C DI SANGGAR KEGIATAN BELAJAR (SKB) KELURAHAN CINTA RAJA KECAMATAN SAIL KOTA PEKANBARU - Rika Hia; Sumardi Sumardi; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the learning motivation of what is the most dominant between intrinsic motivation and extrinsic motivation that encourages citizens to learn about Package C in Sanggar Learning Activities (SKB) of Cinta Raja District in Pekanbaru's Sail City District. The benefits of this study are expected to be a reference material for SKB Managers of Cinta Raja Village, Sail City Pekanbaru Village, regarding the motivation to learn the learning program for C package students in Sanggar Learning Activities (SKB) , Cinta Raja Village, Sail City, Pekanbaru. This research is also useful as a comparison material for other researchers who will conduct research in the same field. This research is descriptive with a quantitative approach. The data collection technique used in this study is a saturated sample technique because this research is the determination of samples if all members of the population are used as samples with a theoretical basis according to Sugiono. The instrument used in this study was a questionnaire containing 46 statements about the motivation to learn the package C program students at the Sanggar Learning Activity (SKB) at the Cinta Raja Village in Sail City District, Pekanbaru, with indicators of intrinsic and extrinsic motivation, consisting of 5 sub indicators divided into 11 dimensions. The results of the data analysis show that the motivation to learn the package C learning program at the Sanggar Learning Activity (SKB) in Cinta Raja District, Sail City District, Pekanbaru, is more intrinsic motivation, seen from the high percentage, mean, and elementary percentage, 70,93 %, 3.78 da 0.91 compared to extrinsic motivation.Keywords: Learning Motivation, Package C Program in Sanggar Learning Activity (SKB)